The medical humanities – How far have we come? - Eng Koon Ong; Wen Shan Sim (The Asia Pacific Scholar)
Introduction: The medical humanities (MH) have the potential to support medical education (ME) by developing observational skills, promote reflective practice and transformative growth. However, contextual content and methods relevant to our local and regional learners and teachers are lacking. Methods: We describe three MH-based ME programmes within SingHealth to illustrate our considerations in the choice of conceptual frameworks and content selection in programme development and evaluation. Results: Highlighting pertinent challenges in developing the field due to poor awareness, lack of resources and research capability, we emphasise the importance of interdisciplinarity, engaging leadership, and generating research output. Broad strategies to achieve these goals are then presented. Conclusion: Highlighting challenges due to the lack of awareness, administrative and funding support, and research capability, we propose strategies to overcome such barriers and hope that readers will be inspired to contribute to this developing landscape where science and art intersect.